Hoffenthal und Umgebung : [ca. 1900] (2001)
Photograph of Hopedale from the hill behind the mission station. A ship, possibly the "Harmony", can be seen anchored in the harbour. Photograph of Hopedale from the hill behind the mission station. A ship, possibly the "Harmony", can be seen anchored in the harbour.